Local Authority Roles in Waste Management: Evidence from Svay Rieng Municipality, Cambodia - Yeng, Rothara; Serey, Mardy; Mom, Ket; Hem, Suntrakwadh; Tum, Saravuth; Hong, Chhun (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
Waste management is a critical challenge in Svay Rieng Municipality, Cambodia, where rapid industrialization and population growth have intensified the problem of uncollected waste. Although national strategies such as the Circular Strategy in Environment Sector 2023–2028 have been introduced, implementation remains limited due to inadequate infrastructure, a small waste collection fleet, weak community participation, and poor coordination among stakeholders. This study employed a qualitative descriptive–interpretive design using a multiple case study approach in Chong Prek and Roup Kor villages. Data were collected through participant observation, semi-structured interviews with twelve key informants, and document analysis, and were validated using triangulation across sources, methods, and investigators. Analysis was guided by the Miles, Huberman, and Saldana model, focusing on the regulatory, facilitative, and dynamizing roles of local authorities. The findings indicate that while regulations exist, enforcement is weak, infrastructure development is delayed by land allocation issues, and outreach efforts are largely reactive. Community engagement remains limited, with participation often triggered only by external pressure or special events. The study concludes that stronger regulatory enforcement, timely infrastructure provision, continuous community education, and institutionalized multi-stakeholder collaboration are essential for advancing a more effective and sustainable waste management system in Svay Rieng Municipality.